Prevalence and burden of chronic cough in China: a national cross-sectional study. Issue 3 (25th July 2022) - Huang, Kewu; Gu, Xiaoying; Yang, Ting; Xu, Jianying; Yang, Lan; Zhao, Jianping; Zhang, Xiangyan; Bai, Chunxue; Kang, Jian; Ran, Pixin; Shen, Huahao; Wen, Fuqiang; et al.
Background: Chronic cough is a common complaint, but there are no population-based data on its burden in China. We determined the prevalence of chronic cough and its impact on health status in adults stratified by sex, age and the diagnosis of COPD or the presence of small airway dysfunction (SAD). Methods: A representative sample of 57 779 Chinese adults aged 20 years or older was recruited and pulmonary function test was measured. Chronic cough was defined as cough lasting for >3 months in each year. Quality of life was assessed by the 12-item Short Form Health Survey (SF-12), and self-reported history of hospital visits was recorded. Results: Chronic cough was found in 3.6% (95% CI 3.1–4.1) of Chinese adults, 2.4% (95% CI 1.9–3.1) of those aged 20–49 years and 6.0% (95% CI 5.3–6.8) of those aged 50 years or older. Individuals with chronic cough had an impaired physical component summary (PCS) score of the SF-12 (p<0.0001) and more emergency visits (p=0.0042) and hospital admissions (p=0.0002). Furthermore, the impact of chronic cough on PCS score was more significant in those aged 50 years or older, or with COPD (p = 0.0018 or 0.0002, respectively), with the impact on hospital admission being more significant in those with COPD or with SAD (p=0.0026 or 0.0065, respectively). Conclusions: Chronic cough is prevalent in China and is associated with a poorer health status, especially in individuals aged 50 years or older and those with the diagnosis of COPD or SAD. In the general adult population in China, chronic cough is prevalent and associated with poorer health status, especially in individuals aged ≥50 years and those with COPD or small airway dysfunction https://bit.ly/3785LYZ